High electrochemical performance of glucose detection based on tapered gold nanostructures and MXene layers - Xianglong Bian; Dong Yang; Yingfei Zeng; Tao Yang; Qianfeng Xia; Tingwei Hu (Sensors and Actuators Reports)
Diabetes disease caused by hyperglycemia has many complications, including cardiovascular disease, kidney disease and visual impairment. Effective and stable platform of enzyme-free glucose detection is significant important for the monitoring of diabetes disease. In this work, uniform single MXene layers were fabricated with large scale through HCl/LiF etching and tapered gold nanostructures (AuTNs) was electrodeposited on the MXene layers. The AuTNs with three-dimensional conical apex on the MXene layers can effectively increase the specific surface ratio and active sites. The composite materials of AuTNs and MXene layers assembled on the glassy carbon electrode (GCE) can significantly increase the electrochemical performance during glucose detection. The modified electrode of AuTNs/MXene/GCE shows good linearity from 0.1 nM to 10.0 mM, low limit of detection (LOD) of 1.43 nM and fast response time of 1.0 s, exhibiting high sensitivity, good stability and high selectivity for glucose during electrochemical detection. The high performance of the modified electrode provides promising potential application in enzyme-free sensor for the electrochemical detection of glucose.